Alteraçãoes fisiológicas e bioquímicas em plântulas de cajueiro anão-precoce submetidas à salinidade em duas condições de cultivo. - Abreu, Carlos Eduardo Braga de (2007)
Early-dwarf cashew seedlings (Anacardium occidentale L.) were used in order to investigate the physiological and biochemical changes induced by salt stress in two environmental conditions. The seedlings were cultivated in plastics pots containing only nutrient solution (control treatment) or nutrient solution with NaCl at 50, 100, 150 and 200 mM (saline treatment). They were kept in two environmental conditions: greenhouse and growth room. The effects of salinity on the growth, gas exchange, chlorophyll content, osmotic potential and organic (proline, soluble amino-N, soluble carbohydrates) and inorganic (Na+, Cl-, K+) solute contents from both leaves and roots were studied. Salt stress induced changes in gene expression were studied both in leaves and roots comparing 2D electrophoretic pattern. Salinity inhibited the growth of seedlings in both environmental conditions, being the reduction in seedlings growth in the greenhouse more conspicuous than those cultivated in the growth room. This fact was correlated with highest reductions in net photosynthetic rate, in transpiration and stomatal conductance of seedlings grown in the greenhouse when compared with those of growth room. In both cultivation conditions, the root growth was affected by NaCl than shoot growth. The salinity stress not caused great changes in CO2 internal concentration, suggesting that the inhibition of photosynthesis also may be attributed to non-stomatal factors. Leaf chlorophyll a, b and total contents were influenced by salinity and environmental conditions, being observed the highest contents and the lowest reductions of these pigments due to salinity in seedlings under growth room conditions. The readings of portable chlorophyll meter, SPAD-502, were positively correlated to leaf chlorophyll contents, expressed in g.cm-2, both in greenhouse and growth room conditions. In the salt stress conditions, the higher reductions of osmotic potential and higher Na+ and Cl- accumulations in leaves were observed in seedlings grown in the greenhouse. On the other hand, leaves K+ contents did not differ much among the cultivation conditions used. The roots accumulated greater amounts of Na+ and Cl- in their tissues, which were accompanied of great decreases in the K+ contents in both cultivation conditions. Proline content increased with the increase in salt stress especially in leaves, being the greater increases observed in seedlings cultivated in the greenhouse. The soluble carbohydrates contents were increased and decreased, due to salinity, only in leaves of seedlings of growth room and roots of those grown in the greenhouse, respectively. In both cultivation conditions, salinity increased the leaf and root soluble amino-N contents of cashew seedlings. The gene expression patterns both leaves and roots were altered by salt stress, in both environmental conditions. Salinity induced increases and decreases in expression of various proteins, being that some proteins disappeared completely and other were apparently synthesized de novo in the seedlings stressed. The proteins differentially regulated by salt stress were enough different among the environmental conditions used. Future studies should be focused on sequencing and identification of proteins whose rate of synthesis varied as a result of salinity, in order to better characterize their possible roles in the process of acclimation of cashew seedlings to salinity conditions.